Promoção de Saúde Bucal para Portadores de Necessidades Especiais - Ferreira, Nancy dos Santos Pinto; Louzada, Liliane Passanezi de Almeida; Lugato, Isabel Cristina Prado Torres; Zito, Ana Rita Albuquerque; Bombonati, Ana Lúcia; Brasil, Rita de Cássia A. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Nancy dos Santos Pinto Ferreira